Online brand attributes and online corporate brand images - da Silva, R. V.; Alwi, S. F. S. (European Journal of Marketing, 2008)
Purpose – The purpose of this paper is to examine which brand attributes need to be emphasised/addressed by retailers in order to achieve a positive representation of the corporate brand images in an online setting. Using bookstores as the research context, the research's main aim is to investigate the association between the functional brand evaluation (represented by brand attributes in this study) and emotional brand evaluation (represented by the corporate brand image). Specific research questions are: Are there any associations between the brand attributes and corporate brand image of an online e?tailer?; What are the most important corporate brand attributes/drivers of online corporate brand image? Design/methodology/approach – Using the brand triangle framework developed by de Chernatony and Christodoulides, the current study investigates the associations between brand attributes and corporate brand image of an online e?tailer. Findings – The findings show that factors such as ease of use, “personalisation”, security and customer care are significant in determining the corporate brand image of the online e?tailer. Practical implications – The practical contribution of the study and its managerial implications are in the provision of strategic directions and positioning the corporate brand in an online context. Originality/value – It has been suggested by recent branding literatures that both functional and emotional brand characterizations should be adopted in order to better model consumer responses. Ailwadi and Keller pointed out that the priority of research should be to understand how corporate brand image and retailer brand attributes interact. The impact of corporate brands on the internet has been the object of study (e.g. Phillips; Lindstrom). The originality of the work is in linking online brand attributes and online corporate brand images and the role of functional and emotional attributes in brand evaluation in an online context.